Clinical Characteristics and Outcomes of Pregnant Women with Covid-19 in Gadjah Mada Academic Hospital - Yosi Tamara; Fithri Islamiyah Sapuraning Rahayu; Rendy Singgih (Universitas Andalas, 2023)
Introduction: This study aimed to determine the characteristics of pregnant women diagnosed withCovid-19 and hospitalized at the Gadjah Mada University Academic Hospital.Methods: The method in this study is a descriptive research method to illustrate a situation objectivelyand without intervention. All pregnant women who seek treatment and are included in the Gadjah MadaUniversity Academic Hospital study are diagnosed with Covid-19 by RT-PCR.Results: The object of this study were 210 pregnant female patients diagnosed with Covid-19 untilAugust 2021. The third trimester dominated the gestational age, and most of them had no symptoms(asymptomatic). The most dominant symptom was cough. Most of the patients came with referrals fromthe puskesmas on the grounds of pregnancy complaints. Most of them are puskesmas referrals withseven days of treatment in the hospital. Most of the delivery of pregnant women with Covid-19 was byabdominal delivery.Conclusion: The clinical characteristics and outcomes of pregnant women with Covid-19 whounderwent treatment varied. Most of them went home from treatment due to improved conditions orhad given birth and continued to self-isolate at home. Nevertheless, it remains a concern that Covid-19is undoubtedly one of the factors that can cause death in pregnant women.